The Effect of Surplus Free Cash Flow and Audit Quality on Earnings Management - Nouri, Saeid; Gilaninia, Behnam (International Journal of Economics and Financial Issues, 2017)
One of the most important management tool is the abuse of free cash flows in those companies with low growth opportunities, companies in which there are lots of free cash flows and moreover there are not much investment opportunities and the corporate governance structure and also the audit quality are not appropriate, rate of using free cash flows increases in order to manage the earnings. So the goal of present investigation is to check the excess effect of free cash flows and audit quality on the earnings management. The period of the present survey is from 2010 to 2014, in which 102 companies have been checked. In this research to test the investigation’s hypothesis, multiple linear regression model and panel data have been used. The analysis results of the first hypothesis free cash flow have positive and significant effect on earnings management. The analysis results of the second hypothesis audit quality have negative and significant effect on the earnings management. The third hypothesis finding, in this research shows that the audit quality has a significant on both surplus free cash flow and earnings management. Keywords: Free Cash Flow, Surplus Free Cash Flow, Earnings Management, Audit Quality. JEL Classifications: M4